Incidence and Risk Factors of Osteonecrosis of Femoral Head in Multiple Myeloma Patients Undergoing Dexamethasone-Based Regimens. (16th May 2020) - Wu, Xinjie; Geng, Chuanying; Sun, Wei; Tan, Mingsheng
Abstract : Objectives . To investigate the incidence and risk factors for osteonecrosis of femoral head (ONFH) in multiple myeloma (MM) patients undergoing dexamethasone-based regimens (DBRs). Methods . A retrospective study was conducted in MM patients administered DBRs between December 2012 and April 2015. Demographic, clinical, and laboratory data were extracted to compare between two groups. Incidence of ONFH were calculated and risk factors identified by both univariate and multivariate analysis. Results . The study group comprised 105 patients undergoing DBRs. Seven patients with ONFH after DBRs were classified as the ONFH group, and the other 98 patients without ONFH were included in the non-ONFH group. Incidence of ONFH was 6.7%. Median age of developing ONFH was 51 years (45–64), and the male to female ratio was 6 : 1. A total of 12 femoral heads were involved, including unilateral in 2 patients and bilateral in 5 patients. After the multivariate analysis, four risk factors were confirmed including male, younger age, cumulative dose of dexamethasone, and hyperlipidemia. Conclusion . The overall incidence of ONFH in MM patients treated with DBRs is 6.7%, and 4 risk factors are confirmed including male, younger age, cumulative dose of dexamethasone, and hyperlipidemia in our study.